THEORETICAL FOUNDATIONS FOR STUDYING REGIONAL INTEGRATION - Shaxobova Shaxzoda Avazovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract.  The  study  of  regional  integration  has  evolved  beyond  the universalization of the Western European model. Contemporary scholars highlight the need  for  comprehensive  theoretical  frameworks  that  consider  historical,  political, economic, and socio-cultural dimensions. This article presents a critical overview of classical  and  contemporary  integration  theories,  examining  their  explanatory, descriptive, and prescriptive roles in understanding regional integration processes.